A Digital Service Supply Chain Model for ASEAN University Network Quality Assurance at Institutional Level - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research about a service supply chain model in digital for ASEAN University Network Quality Assurance at institution level. The objectives of research to design and to assess the suitability of a service supply chain model in digital for ASEAN University Network Quality Assurance at institution level. The sample group consisted of fifteen experts in the field of information system ,supply chain and research. The data is analyzed by means and standardized deviations statistically. The research result shows that a service supply chain model in digital for ASEAN University Network Quality Assurance at institution level. is consisted of 8 key elements which are 1) main elements 2) suppliers /services 3) university 4) customers 5)consumer 6 Satisfaction 7 Feedback. The results from fifteen expert a service supply chain model in digital for ASEAN University Network Quality Assurance at institution level. was a high level which mean that It could be used to service digital quality assurance for ASEAN University Network Quality Assurance